Analysis of genetic diversity and population structure of Babesia gibsoni - Yin, Fangyuan; Guo, Chuanjiang; Tian, Zhuojia; Li, Dong; Mu, Daoe; Liu, Haoting; Guan, Guiquan; Yin, Hong; Li, Facai (Frontiers in Veterinary Science, 2023)
Babesia gibsoni is a tick-borne apicomplexan protozoan causing canine babesiosis. This parasite has diploid sexual reproduction in ticks, during which genetic exchanges can occur leading to increased genetic diversity, which is an important factor in adapting to environmental changes. Exploring the genetic variation of B. gibsoni population can provide a foundation for understanding the patterns of disease transmission and developing babesiosis control strategies. Partial 18S rRNA fragment sequences were obtained from 11 B. gibsoni isolates collected from different regions in China and 117 publicly available sequences were from 12 geographical areas including China. The genetic variation, demographic expansion and population structure were examined. A total of 34 haplotypes were identified among B. gibsoni populations. Analysis of molecular variance, pairwise Fst and structure analysis showed that high genetic variation within populations, low genetic differentiation and obvious mixture haplotype were apparent in a single continent, but higher genetic differentiation was detected across different continents. Neutrality tests implied that B. gibsoni populations had experienced population extension. These findings will contribute to understand the genetics and evolution of B. gibsoni and will be useful for formulating effective management strategies to prevent and control this parasite.